THE EFFECT OF GADGETS ON CHILDREN'S DEVELOPMENT - M. Dimas Aldy (JEBS (Journal of Economic and Business Student), 2023)
Currently, early childhood is already using gadgets that are used to spend their playing time. The purpose of this study was to determine the effect of the length of time using gadgets in early childhood on social development. This research method is observational analytic. The variables of this study are the duration of using gadgets and social development. The results of the statistical test research show that there is a difference or influence of the duration of using gadgets on social development. In conclusion, there is a long influence of using gadgets in children on social development in their environment.